Kaum Injili dan Pericope Adulterae (Yoh. 7:53-8:11): Sebuah Usulan - Stefanus Kristianto (SOLA GRATIA: Jurnal Teologi Biblika dan Praktika, 2022)
Abstract:  Pericope Adulterae, commonly known as “The Story of the Adulterous Woman” (John 7:53-8:11), is one of the famous stories in the Gospel of John. However, this story turns out to have serious problems regarding its authenticity. So, how should Evangelicals deal with this passage? This paper will begin with a textual analysis to show that the Pericope Adulterae is not an integral part of the Gospel of John. Afterwards, the authors turn to historical analysis to show that Pericope Adulterae probably originated from an oral tradition that was then preserved in three different written forms. Lastly, the writer tries to look at this text from a theological perspective, especially the Evangelical doctrine of inspiration. The author concludes that Pericope Adulterae is not part of the inspired word of God. Therefore, this passage should not be the norma normans for the Evangelicals. However, this passage is a beautiful legacy of church tradition, which to some extent can still be used in the spiritual life of the Evangelicals.  Abstrak: Pericope Adulterae, atau yang lazim dikenal sebagai “Kisah Perempuan yang Berzinah” (Yoh. 7:53-8:11), adalah salah satu kisah terkenal dalam Injil Yohanes. Meski demikian, kisah ini ternyata memiliki problem serius mengenai autentisitasnya. Lantas, bagaimanakah Kaum Injili harus menyikapi perikop ini? Tulisan ini akan mulai dengan analisa tekstual untuk menunjukkan bahwa Pericope Adulterae bukanlah bagian integral dari Injil Yohanes. Selanjutnya, penulis berpindah ke analisa historis untuk menunjukkan bahwa Pericope Adulterae kemungkinan berasal dari tradisi lisan yang lantas dipelihara dalam tiga bentuk tertulis yang berbeda. Terakhir, penulis mencoba memandang teks ini dengan kacamata teologis, khususnya doktrin Kaum Injili mengenai inspirasi. Kesimpulan penulis, Pericope Adulterae bukan bagian dari firman Allah yang diinspirasikan. Karena itu, bagian ini tidak seharusnya menjadi norma normans bagi Kaum Injili. Meski demikian, perikop ini adalah warisan yang indah dari tradisi gereja, yang dalam batas tertentu masih bisa digunakan dalam kehidupan rohani Kaum Injili.